Deepfake and the Admissibility of Digital Evidence in Syiqaq Cases: Challenges for Islamic Family Law in the Generative AI Era - Ahmad (PT Taskuliah Edukasi Indonesia, 2026)
The rapid advancement of digital technology has transformed evidentiary practices in Indonesia's judicial system, including the adjudication of syiqaq (marital dispute) cases within the Religious Courts. Digital traces are increasingly recognized as qarīnah (circumstantial evidence); however, the emergence of Generative Artificial Intelligence (GenAI) and deepfake technology has raised unprecedented challenges regarding the authenticity and reliability of digital evidence. This study examines the implications of deepfake technology for the admissibility of digital evidence in syiqaq cases and proposes a reconstruction of evidentiary standards from the perspective of Islamic family law. Employing a socio-legal approach, the study combines doctrinal analysis of Indonesian positive law, Islamic legal principles, and contemporary judicial practices concerning digital evidence. The findings reveal a regulatory gap in addressing synthetic media, creating the risk of the Liar's Dividend phenomenon, whereby authentic evidence may be dismissed while manipulated evidence is erroneously accepted. The study argues that the Qur'anic principle of tabayyun should be operationalized through standardized digital forensic authentication and integrated with the framework of maqāṣid al-sharīʿah to safeguard family integrity (ḥifẓ al-nasl) and personal honor (ḥifẓ al-ʿirḍ). This study contributes to the evolving epistemology of bayyinah by proposing a normative framework for reforming digital evidentiary standards in the era of Generative AI. [Perkembangan teknologi digital telah mengubah praktik pembuktian dalam peradilan Indonesia, termasuk dalam penyelesaian perkara syiqaq di lingkungan peradilan agama. Jejak digital kini semakin diterima sebagai qarīnah (circumstantial evidence), tetapi kemunculan Generative Artificial Intelligence (GenAI) dan teknologi deepfake menimbulkan tantangan baru terhadap autentisitas dan reliabilitas alat bukti digital. Penelitian ini bertujuan menganalisis implikasi deepfake terhadap keberterimaan alat bukti digital dalam perkara syiqaq serta merekonstruksi standar pembuktian berdasarkan prinsip hukum keluarga Islam. Penelitian menggunakan pendekatan sosio-legal melalui analisis doktrinal terhadap hukum positif Indonesia, prinsip-prinsip hukum Islam, dan perkembangan praktik pembuktian digital di peradilan. Hasil penelitian menunjukkan adanya kekosongan pengaturan mengenai autentikasi media sintetis yang berpotensi memunculkan fenomena Liar's Dividend, yaitu kondisi ketika bukti autentik diragukan atau bukti hasil manipulasi justru diterima sebagai alat bukti. Oleh karena itu, prinsip tabayyun perlu dioperasionalkan melalui mekanisme autentikasi forensik digital yang terstandar dan diintegrasikan dengan pendekatan maqāṣid al-sharī‘ah untuk melindungi keutuhan keluarga (ḥifẓ al-nasl) dan kehormatan (ḥifẓ al-'irḍ). Penelitian ini berkontribusi pada pengembangan epistemologi bayyinah dalam hukum keluarga Islam dengan menawarkan kerangka normatif bagi pembaruan standar pembuktian digital pada era GenAI].